До правових питань діяльності стартапів в умовах збройної агресії Російської Федерації проти України (російсько-української війни) - Коритін, Д. С. (НДІ ПЗІР НАПрН України, 2022)
Стартапи, як новостворені суб’єкти інноваційної діяльності, стикаються з низкою проблем правового характеру. Питання, які постають перед стартапом, залежать від етапу розвитку, на якому в даний час він перебуває. У статті розглянуто правові питання, з якими може стикнутися стартап на етапі Early Growth в аспекті збройної агресії РФ проти України, оскільки на вказаному етапі стартап діє як офіційно зареєстрований у передбаченому законом порядку суб’єкт підприємницької діяльності і, відповідно, на нього розповсюджується дія низки нормативно-правових актів, що регулює діяльність таких суб’єктів. Зокрема, у статті було розглянуто питання, які можуть виникнути у сфері зобов’язального права в аспекті введення в Україні військового стану, а також зміни у податкову законодавстві, спрямовані на сприяння підприємницької діяльності платників податків. Зроблено висновок, що більшість стартапів України, що перебувають на початковій стадії виведення та реалізації інноваційної продукції на ринку, стикаються з проблемами неможливості повного виконання взятих на себе зобов’язань або ускладненням процесу ведення бізнесу. Наша держава створює умови для спрощеної реалізації процедури звільнення стартапів від відповідальності за невиконання або неналежне виконання взятих на себе обов’язків за договорами, за умови коли таке невиконання напряму пов’язано з існуванням обставин непереборної сили у вигляді збройної агресії РФ проти України. Крім того, Верховною Радою України внесено зміни до податкового законодавства, за якими, зокрема, надано підтримку найбільшій (третій) групі спрощеної системи оподаткування та розширено перелік суб’єктів, які можуть бути включені до такої групи оподаткування. Вказані зміни спрямовані на стимулювання осіб до здійснення підприємницької діяльності у цей надзвичайно складний етап розвитку нашої держави і створення фундаменту для післявоєнної економічної відбудови та відродження України. Problem setting. The armed attack of the Russian Federation on Ukraine without a declaration of war, which took place at 5 am on February 24, 2022, at the same time radically changed the entire system of legal relations of our state. The unification of the whole nation (in the political sense of the term) against the unprecedented criminal actions of the “fraternal people” caused a temporary cessation (or modification) of the usual daily work of every citizen, foreigner or stateless person. Undoubtedly, business representatives, including startups, have been providing significant support for the resistance of our state to armed aggression since the first days. Realizing the value of such assistance and the importance of business entities for Ukraine, public authorities have developed and adopted a number of regulations aimed at updating legal relations with such entities. Analysis of resent researches and publications. Issues of startup activity have become the subject of research by such scientists as SV Glebko OV Rozgon, IV Podrez-Ryapolova, AS Petkevich, AV Sherstobitov, IV Yashchyshina and others. Within the framework of this scientific article, the specifics of the activities of startups in a state of martial law caused by an act of armed aggression of the Russian Federation against our state will be studied. The target of research is to study the legal issues of startups in the Russian-Ukrainian war. In this regard, we consider it appropriate in this article to focus on startups that are at the stage of Early Growth, because at this stage the startup acts as an officially registered business entity and, accordingly, it a number of normative legal acts regulating the activity of such subjects are extended. Article’s main body. As we have repeatedly mentioned before, a startup is an innovative idea or a newly created business entity (individual entrepreneur or legal entity). According to the officials of the international ecosystem Startup-Network, the main feature that distinguishes a startup from a normal small or medium enterprise is the mandatory trend of the startup to develop and further transform into a large enterprise. Agreeing with this feature, we consider it appropriate to supplement the characteristics of the startup with another mandatory feature innovation. This feature directly follows from the analysis of the legislation of European countries, international acts, EU documents and reference materials of a number of international organizations. Thus, based on the above mandatory features of startups, it follows that a startup goes through a number of stages of its formation and development. This research will address the issue of startups at the Early Growth stage. At this stage, the startup usually has the status of a small or medium enterprise and needs comprehensive government support. Startups in Ukraine that have faced the problem of fulfilling their commitments can now use the simplified procedure for obtaining a certificate from the Chamber of Commerce and Industry of Ukraine. However, it should be borne in mind that obtaining confirmation of the existence of force majeure does not in itself release you from liability for nonperformance or improper performance of obligations. There is a need to prove a direct and irreversible causal link between such circumstances and the inability to perform duties. In addition, in the field of international relations, it is necessary to take into account the existence of a number of international acts that regulate the consequences of force majeure. Changes in tax legislation concerning startups in the third group of the simplified taxation system are that, on the one hand, the tax burden on the business entity has been reduced, and on the other hand, the frequency of tax revenues has been reduced. Conclusions and prospects of the development. Most startups in Ukraine, which are at the initial stage of launching and selling innovative products on the market, face problems of inability to fully meet their commitments or complicate the process of doing business. Our state creates conditions for simplified implementation of the procedure of releasing startups from liability for non-performance or improper performance of their obligations under contracts, provided that such non-performance is directly related to the existence of force majeure in the form of armed aggression against Ukraine. In addition, the Verkhovna Rada of Ukraine amended the tax legislation, which, in particular, provided support to the largest (third) group of the simplified taxation system and expanded the list of entities that can be included in such a group of taxation. These changes are aimed at encouraging people to do business in this extremely difficult stage of development of our state and creating a foundation for postwar economic reconstruction and revival of Ukraine.
Keywords: стартап; МСП; виконання зобов’язань; оподаткування; військовий стан; startup; SMEs; fulfillment of obligations; taxation; martial law